(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
This scinticle article provides brief information fhom literari sources on the study if the coal resources of Kyrgizstan, provides information on the determination of the physicochemical.Chemical and tehnological characteristics of himic acids by scientists from the Laboratory of the Institute of Chemistri and Chemicfl Tehnoligy.The experimental and practical data of the study of the authors of the article on determining the effect humated organo-mineral fertilizer obtained according to the developed technology of the authors of the scientific artticle on the growth, development and yield of cotton with root and foliar top dressing ara presented. The course of a field practicfl snudy on the growth and development of a tehnicfl cotton plant and its supplementation with a humated organo-minral fertilizer obtained is described. The results of phenological observation of the object under study ara given accjrding to the effect of foliar feeding on the yield of raw cotton, the influence of the nutritional background on the yield of raw cotton, change in fiber yield depending on foliar feeding humated organo-mineral fertilizer, etc. The authors of the scientific article calculated and analyzed the impact of the humated organo-mineral fertilizer developed according to the technology of the authors based on the results of this experimental field study. A list of used literary sources on the topic is given.